"I can live with nuclear energy if…": Exploring public perceptions of nuclear energy in Singapore. (September 2018) - Ho, Shirley S.; Looi, Jiemin; Chuah, Agnes S.F.; Leong, Alisius D.; Pang, Natalie
Abstract: Considering the growing salience of nuclear energy in Southeast Asia, this study examines public perceptions of nuclear energy in Singapore, a technologically-advanced and affluent nation well-equipped to develop nuclear energy capabilities. Drawing from the source credibility theory, this study examines the public's credibility perceptions of nuclear-related information sources, and their trust in potential stakeholders. Guided by the psychometric paradigm, this study also explores public perceptions of risks, benefits, and support. Four focus group discussions were conducted with Singaporeans aged 18–69. Participants across different age groups (e.g., Millennials, Generation X, Baby Boomers) concurred in their trust of potential stakeholders, risk perception, cost perception, and support. Intergenerational differences were observed for participants' media use, credibility perceptions of nuclear-related information sources, and benefit perception. This study contributed theoretically by applying the source credibility theory and psychometric paradigm in an under-studied context. Practical implications were provided for policymakers and communication practitioners to effectively evaluate public awareness and acceptance for nuclear energy. Directions for future research were discussed. In conclusion, intergenerational similarities were observed for Singaporeans' perceptions of risks, costs, and support. Meanwhile intergenerational differences were noted for their credibility perceptions of nuclear-related information sources, trust in potential stakeholders, and benefit perception. Highlights: Focus group discussions were conducted with Singaporeans aged 18–69. Generations differed in their media use and perceived credibility of online media. Nuclear accidents mentioned most frequently across generations as a potential risk. Generations differed by mentioning certain benefits of nuclear energy more frequently. General opposition for nuclear energy, but conditional acceptance for several reasons.